Development of an impact model for institutional research productivity - Marcial, Victoria Gonzales (1995)
This study described and evaluated the impact on the productivity of the research program of selected SUCs in the Calabarzon of Region IV. Single-case design with a criteria-referenced survey analysis and a round table discussion were used as sources of data. An analogue model was developed to measure the impact of the research process. Outcomes of the research in the institution were idicators of impact of management of the research process. The impact model measures the impact of the management of institutional research process to efficiently use relevant inputs, generate, conduct, evaluate, maintain, and periodically renew activities.
Computer print-out.
Thesis (Ph. D.)--University of the Philippines, Diliman.
Keywords: Education, Higher -- Research; Research institutes -- Philippines -- Calabarzon; Universities and colleges -- Research. -- Philippines